2022
DOI: 10.2147/ijwh.s343065
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sexual Dysfunction in Women with Type 1, 2 Diabetes and Thyroid Disorder: A Cross-Sectional Study in Taif City, Saudi Arabia

Abstract: Background Women with diabetes mellitus or thyroid disorders are at risk of sexual dysfunction. This study aimed to estimate the prevalence of female sexual dysfunction (FSD) in women with diabetes and/or thyroid disorders and the impact of disease control on the ASEX score. Methods A cross-sectional study for female patients who had a routine clinic visits was included. The Arizona Sexual Experience Scale (ASEX) was used to evaluate for FSD. Those with a total score of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
2
0
0
Order By: Relevance
“…Our study observed high prevalence of SD among diabetic patients who were already living with any form of complication of diabetes such as diabetic nephropathy, neuropathy, or retinopathy, and our observations are well supported by the findings of various previous studies of Gandhi et al, [8] Vafaeimanesh et al, [20] Binmoammar et al, [21] Ugwu et al, [22] Alshehri et al, [23] and Gupta et al [24] Drive > overall satisfaction > arousal > orgasm > erection was type of SD among males and drive > orgasm > arousal > overall satisfaction > lubrication was type of SD among females in our study. However, contrary to our study, orgasm disorder and arousal were domains most affected in study by Getie Mekonnen et al [12] whereas lubrication and orgasm were domains most affected in study by James Paningbatan et al [11] With similarity to our study, drive, arousal, lubrication, satisfaction, and orgasm were domains affected in that order in study of Rahmanian et al [25] These differences may be due to various locoregional influences, intricating and difficult to understand definitions of various components of sexual cycle.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our study observed high prevalence of SD among diabetic patients who were already living with any form of complication of diabetes such as diabetic nephropathy, neuropathy, or retinopathy, and our observations are well supported by the findings of various previous studies of Gandhi et al, [8] Vafaeimanesh et al, [20] Binmoammar et al, [21] Ugwu et al, [22] Alshehri et al, [23] and Gupta et al [24] Drive > overall satisfaction > arousal > orgasm > erection was type of SD among males and drive > orgasm > arousal > overall satisfaction > lubrication was type of SD among females in our study. However, contrary to our study, orgasm disorder and arousal were domains most affected in study by Getie Mekonnen et al [12] whereas lubrication and orgasm were domains most affected in study by James Paningbatan et al [11] With similarity to our study, drive, arousal, lubrication, satisfaction, and orgasm were domains affected in that order in study of Rahmanian et al [25] These differences may be due to various locoregional influences, intricating and difficult to understand definitions of various components of sexual cycle.…”
Section: Discussionsupporting
confidence: 91%
“…Our study observed high prevalence of SD among diabetic patients who were already living with any form of complication of diabetes such as diabetic nephropathy, neuropathy, or retinopathy, and our observations are well supported by the findings of various previous studies of Gandhi et al , [8] Vafaeimanesh et al, [20] Binmoammar et al, [21] Ugwu et al , [22] Alshehri et al, [23] and Gupta et al [24]…”
Section: Discussionsupporting
confidence: 90%
“…It can be attributed also to past sexual history (as early sexual experience or early marriage before 18 years old, poor sexual education, exposure to pornographic content, and/or sexual assaults or violence) [3] , [4] . Sexual dysfunction also exhibited a strong correlation with smoking [5] , genitourinary infections, sexually transmitted diseases, neuroses [6] , multiple sclerosis, bronchial asthma [7] , diabetes type-I, Diabetes type-II [8] , infertility, and pelvic floor dysfunctions [9] . Women’s quality of life is substantially improved by screening, diagnosing, and controlling associated illness [10] .…”
Section: Introductionmentioning
confidence: 99%